2010
DOI: 10.1111/j.1468-2494.2010.00610.x
|View full text |Cite
|
Sign up to set email alerts
|

Expert opinion and review article: The timing of comedone extraction in the treatment of premenstrual acne – a proposed therapeutic approach

Abstract: Synopsis The face is the most exposed part of our body, and deterioration of facial appearance, through disease or ageing, causes psychological distress. Acne lesions and subsequent pigmentation changes contribute to the unevenness of skin colour that is detrimental to facial attractiveness and leads to rejection and stigmatization in our society. The purpose of this review is to look at the root causes of premenstrual acne and, for the first time ever, propose that the specific timing of treatment can, at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 68 publications
(96 reference statements)
1
24
0
1
Order By: Relevance
“…Dermatoses such as atopic and contact dermatitis, psoriasis, acne and even EM and solitary fibrous tumour may be exacerbated premenstrually or perimenstrually . Nearly half of all patients with atopic eczema experience deterioration in their condition in the week prior to the menstruation, with the exacerbation rapidly settling after the onset of menstrual flow .…”
Section: Other Dermatoses Exacerbated By Menstruationmentioning
confidence: 99%
“…Dermatoses such as atopic and contact dermatitis, psoriasis, acne and even EM and solitary fibrous tumour may be exacerbated premenstrually or perimenstrually . Nearly half of all patients with atopic eczema experience deterioration in their condition in the week prior to the menstruation, with the exacerbation rapidly settling after the onset of menstrual flow .…”
Section: Other Dermatoses Exacerbated By Menstruationmentioning
confidence: 99%
“…Mechanical procedures Mechanical procedures include comedone extraction, cautery, hyfrecation and dermabrasion, and intralesional injection of steroids. A recent study in adult females with premenstrual acne found that comedone extraction at the time of ovulation may contribute to a reduction in inflammatory lesions 67 . Dermabrasion is effective for the revision of atrophic acne scars in patients treated with isotretinoin, 68 and also when used in combination with chemical peels 69 .…”
mentioning
confidence: 99%
“…Because sebaceous gland growth and sebum production are controlled by sex hormones, sebum secretion becomes abundant and Fordyce's spots increase after puberty. While androgens increase sebaceous gland size and sebum production, estrogen and progesterone suppress sebum production . Therefore, sebum production and secretion are altered during the menstrual cycle in women.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, sebum production and secretion are altered during the menstrual cycle in women. Increased sebum affects the skin microflora and inflammation may occur subsequently . An exacerbation of acne vulgaris during the late luteal phase is sometimes observed in women .…”
Section: Discussionmentioning
confidence: 99%